Age- and sex-specific differences in myocardial sympathetic tone and left ventricular remodeling following myocardial injury - Achi Haider; Susan Bengs; Angela Portmann; Sandro Fröhlich; Dominik Etter; Monika Maredziak; Geoffrey I. Warnock; Alexander Akhmedov; Sebastian Kozerke; Claudia Keller; Fabrizio Montecucco; Bruno Weber; et al. (Biology of Sex Differences)
Abstract Background Presentations and outcomes of acute myocardial infarction (MI) differ between women and men, with the worst outcomes being reported in younger women. Mental stress induced ischemia and sympathetic activation have been suggested to play a prominent role in the pathogenesis of MI in younger women, however, the impact of sex hormones on these parameters remains unknown. Methods The effect of sex hormones and age on myocardial infarct size and myocardial sympathetic activity (MSA) was assessed in male and female, as well as young (4–6 months) and aged (20–22 months) FVB/N mice (n = 106, 60 gonadectomized and 46 sham-operated animals) who underwent in vivo [11C]meta-hydroxyephedrine ([11C]mHED) positron emission tomography (PET) and cardiac magnetic resonance (CMR) imaging 24 h after a 30 min myocardial ischemic injury. Results MSA and catecholamine levels following myocardial injury were highest in young males (p = 0.008 and p = 0.043 vs. young females, respectively) and were reduced by orchiectomy. Accordingly, testosterone serum levels correlated positively with MSA (r = 0.66, p < 0.001). Males had a larger average infarct size and lower left ventricular contractility following myocardial injury than females (p < 0.05 vs. females). These sex differences were no longer evident in gonadectomized animals (p = NS vs. females). In female animals, estrogen depletion did not affect MSA (ovariectomy effect, p = 0.892). Female animals showed an age-dependent increase in MSA (p = 0.011), which was absent in males. Conclusion Testosterone associates with an increase in sympathetic tone, contributing to adverse cardiac remodeling following MI. Conversely, females maintain sympathetic integrity, independent of sex hormones. Our results suggest a biological advantage of female sex in post MI recovery. Further research is warranted to confirm these findings in humans.